Individually tailored whole-body vibration training to reduce symptoms of chemotherapy-induced peripheral neuropathy: study protocol of a randomised controlled trial—VANISH. Issue 4 (24th April 2019) - Streckmann, Fiona; Hess, Viviane; Bloch, Wilhelm; Décard, Bernhard F; Ritzmann, Ramona; Lehmann, Helmar C; Balke, Maryam; Koliamitra, Christina; Oschwald, Vanessa; Elter, Thomas; Zahner, Lukas; Donath, Lars; et al.
Abstract : Introduction: Chemotherapy-induced peripheral neuropathy (CIPN) is a prevalent and clinically meaningful side effect of cancer treatment. CIPN is induced by neurotoxic agents, causing severe sensory and/or motor deficits, resulting in disability and poor recovery, reducing patients' quality of life and limiting medical therapy. To date, effective treatment options are lacking. Whole-body vibration (WBV) training can attenuate motor and sensory deficits. We are conducting a two-armed, multicentre, assessor-blinded, randomised controlled trial, to investigate the effects of WBV on relevant symptoms of CIPN and determine the training characteristics. Methods and analysis: In this ongoing study, 44 patients who have completed therapy in the past 3 months, with a neurologically confirmed CIPN are assessed before and after a 12-week intervention and follow-up. The intervention group receives WBV twice a week. Exercises are individually tailored according to the initially determined optimal neuromuscular response. The control group receives care as usual. Primary endpoint is the patient reported reduction of CIPN-related symptoms (Functional Assessment of Cancer Therapy/Gynaecology Oncology Group—Neurotoxicity). Secondary endpoints are compound muscle action potentials, distal motor latency, conduction velocity, F-waves from the tibial and peroneal nerve, antidromic sensory nerve conduction studies of the sural nerve, normalised electromyographic activity, peripheral deep sensitivity, proprioception, balance, pain, the feasibility of training settings, quality of life and the level of physical activity. Aim, ethics and dissemination: The study was approved by both responsible ethics committees. (1) Our results may contribute to a better understanding of the effects of WBV on motor and sensory functions and (2) may provide information whether WBV at the most effective setting, is feasible for neuropathic patients. (3) Our results may also contribute to improve supportive care in oncology, thereby enhancing quality of life and enabling the optimal medical therapy. All results will be published in international peer-reviewed journals as well as a manual for clinical practice. Trial registration number: NCT03032718